Advance of signal transduction pathways in normal cell. Issue 2 (28th September 2016) - Zhang, Chao; Zhu, Yu‐Hang; Liu, De‐Xing; Zhu, Zhao‐Qiong
Abstract : Signal transduction pathways are very important for the survival of organisms. Any disturbance of these pathways could induce diseases. For better understanding these diseases to get more benefits for patients, it is necessary to fully understand the signal transduction pathway in a normal cell. Therefore, we summarized these related pieces of literature and introduced the main two kinds of signal transduction pathways.